1988
DOI: 10.1007/bf01914359
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of thio-and selenocyanatocopper(II) complexes with bipyridine and phenanthroline

Abstract: The paper deals with the thermal properties of complex compounds of the general formula CuL2(NCX)2 (where L = bipy or phen, X = S or Se). The phenanthroline complexes exhibit a higher thermal stability than those with bipyridine. For the latter complexes thermal decomposition begins with the release of bipyridine molecules, while for the phenanthroline complexes redox ,reactions of pseudohalogenide ligands with Cu(II) take place. The redox reactions start at a lower temperature for the selenocyanate complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…An analogous course of thermal decomposition was also observed for [Cu(bipy)2(NCX)](NCX) (X=S or Se) [3]. It was found that the thermal stabilities of the complexes were found to increase in the order py<<bipy<phen ligands.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…An analogous course of thermal decomposition was also observed for [Cu(bipy)2(NCX)](NCX) (X=S or Se) [3]. It was found that the thermal stabilities of the complexes were found to increase in the order py<<bipy<phen ligands.…”
supporting
confidence: 62%
“…An analogous course of thermal decomposition was also observed for [Cu(bipy)2(NCX)](NCX) (X=S or Se) [3]. The decomposition temperature of thiocyanate ligands depends on the properties of the ligands L present in the coordination sphere.…”
supporting
confidence: 56%
“…Notwithstanding, the metal coordination of the {NCSe} − group might be unstable, resulting in decomposition into the cyanide ion and selenium atom; this reaction was previously reported with copper(II) acetate [ 24 , 25 ] and was exploited for catalytic purposes in cyanation reactions. Selenocyanate to cyanide degradation was also observed in human blood, and the ferric ion is typically involved in this process [ 26 ].…”
Section: Introductionmentioning
confidence: 98%